The last to vanish : [large type] a novel - Miranda, Megan (Wheeler Publishing, a part of Gale, a Cengage Company, 2022)
"Ten years ago, Abigail Lovett fell into a job she loves, managing The Passage Inn, a resort nestled in the North Carolina town of Cutter's Pass. Cutter's Pass is best known for its outdoor offerings and its mysterious history. The string of disappearances that has haunted the town is once again thrust into the spotlight when journalist Landon West, who was staying at the inn to investigate the story of the vanishing trail, the disappears himself. When Abby finds incriminating evidence that may bring them closer to the truth, Abby discovers how little she knows about her coworkers, neighbors, and even those closest to her"--